An Analysis of Students Difficulties in Pronouncing English Vowels in Their Speaking Skills Based On Mother Tongue - Dini Yuliansih1; Aa Qonaatun2; Fadilla Oktaviana (English Education, Linguistics, and Literature Journal, 2022)
Abstract: Many students are difficult to pronounce the word especially in English language and pronunciation as basic of all English skills, without correct pronunciation students’ will do miscommunication between speakers and listeners. The writer interested to make the research about An Analysis of Students’ Difficulties in Pronouncing English Vowels in Their Speaking Skills Based on Mother Tongue at the First Grade of SMAN 6 Kota Serang. The objectives of the research were to find what are the vowels difficulties, to know what kind of Students’ mother tongue which has high difficulties in pronouncing English vowels and to know the factors of the students’ difficulties. The result of the research shows the students difficulties in pronouncing English vowels in their speaking skill based on mother tongue. The writer used the instrument of collecting data by using test and interview. The result of the research shows the students difficulties in pronouncing English vowels in their speaking skill based on mother tongue. The writer used the instrument of collecting data by using test and interview. The students can speak English but the Students’ still difficult to pronounce the word of English and one of the factors Students’ difficulties in pronouncing English vowels is caused by students’ mother tongue has.